High‐Speed Modulator Based on Electro‐Optic Polymer Infiltrated Subwavelength Grating Waveguide Ring Resonator. Issue 6 (17th May 2018) - Pan, Zeyu; Xu, Xiaochuan; Chung, Chi‐Jui; Dalir, Hamed; Yan, Hai; Chen, Ke; Wang, Yaguo; Jia, Baohua; Chen, Ray T.
Abstract: Silicon‐organic hybrid integrated devices show great potential in high‐speed optical interconnects and sensors. In this paper, a high‐speed modulator based on an electro‐optic (EO) polymer (SEO125) infiltrated sub‐wavelength grating (SWG) waveguide ring resonator is presented. The core of the SWG waveguide consists of periodically arranged silicon pillars along the light propagation direction, which provides large mode volume overlap with EO polymer. The optimized SWG shows a mode volume overlap of 36.2% with a silicon duty cycle of 0.7. The 3‐dB modulation bandwidth of the fabricated modulator is measured to be larger than 40 GHz occupying an area of 70 μm x 29 μm, which is the largest bandwidth and the most compact footprint that has been demonstrated for ring resonators on the silicon‐organic hybrid platform. Abstract : A high‐speed modulator based on an electro‐optic (EO) polymer infiltrated sub‐wavelength grating (SWG) waveguide ring resonator is presented. The 3‐dB modulation bandwidth of the fabricated modulator is measured to be larger than 40 GHz occupying an area of 70 μm × 29 μm, which has a large bandwidth and a very compact footprint compared with the ring resonators demonstrated on the silicon‐organic hybrid platform.